2014
DOI: 10.1016/j.cub.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Glucose Depletion Immobilizes Active Myosin V on Stabilized Actin Cables

Abstract: Summary Polarization of eukaryotic cells requires organelles and protein complexes to be transported to their proper destinations along the cytoskeleton [1]. When nutrients are abundant, budding yeast grows rapidly transporting secretory vesicles for localized growth and actively segregating organelles [2, 3]. This is mediated by myosin-Vs transporting cargos along F-actin bundles known as actin cables [4]. Actin cables are dynamic structures regulated by assembly, stabilization and disassembly [5]. Polarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…To compare our findings with published data on actin distribution in fixed 9 and live glucose-starving cells 2425 we employed image analyses of wild-type rho + (respiring) cells expressing established fluorescence markers of the two different F-actin structures patches and cables (Abp1-RFP and Abp140-GFP). Both the glucose-grown and the glucose-depleted cells were fixed with 3.7 % formaldehyde for 30 minutes, and changes in distribution of both markers Abp1-RFP and Abp140-GFP were analyzed (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…To compare our findings with published data on actin distribution in fixed 9 and live glucose-starving cells 2425 we employed image analyses of wild-type rho + (respiring) cells expressing established fluorescence markers of the two different F-actin structures patches and cables (Abp1-RFP and Abp140-GFP). Both the glucose-grown and the glucose-depleted cells were fixed with 3.7 % formaldehyde for 30 minutes, and changes in distribution of both markers Abp1-RFP and Abp140-GFP were analyzed (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…First, we tested if the QUEEN ratio, indeed, reflects the cellular concentration of ATP in living yeast cells. A previous biochemical study has demonstrated that ATP levels in budding yeast cells dropped to 15% upon glucose depletion and gradually recovered to 50% of the original level within 20 min (Xu and Bretscher, 2014). Moreover, replacement of glucose in medium with 2-deoxy-Dglucose (2DG), which strongly inhibits glycolysis, reduced cellular ATP levels to <1% at least for 30 min (Serrano, 1977;Xu and Bretscher, 2014).…”
Section: Queen Is a Reliable Atp Biosensor In Budding Yeast Cellsmentioning
confidence: 99%
“…Second, we tested if QUEEN can reversibly monitor a change in ATP concentration. We took advantage of gph1Δ mutant cells that cannot catabolize glycogen and do not show any recovery of ATP after glucose depletion (Xu and Bretscher, 2014). The mean QUEEN ratios in glucose-depleted gph1Δ cells declined rapidly within 10-15 min, but re-feeding of glucose fully recovered these values within a minute ( Fig.…”
Section: Queen Is a Reliable Atp Biosensor In Budding Yeast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Yu et al revealed the different dynamics and motility of cables in polarized and unpolarized cells in the exponential phase (30). Additionally, in vivo observations of cables under conditions of acute glucose depletion revealed the stabilization of cables (31), albeit previous observations of fixed cells detected the persistence of depolarized patches only (32). This in vivo approach has not yet been used for monitoring of actin cables in post-diauxic and stationary phases.…”
mentioning
confidence: 99%